Analisis Location Quotient (LQ) Pada Tanaman Hias di Kecamatan Cidahu Kabupaten Sukabumi - ningrum, astria candra (Universitas Veteran Bangun Nusantara, 2025)
Plants that have special characteristics, one of which is ornamental plants, almost all regions in Indonesia are planted with ornamental plants. Of course, each region has different potential and characteristics, so it is necessary to identify the superior potential that exists in the area. The research objective is to analyse the Location Quotient LQ on ornamental plants in Cidahu District. The method used is location quotient LQ analysis, the research location is located in Cidahu District, Sukabumi Regency. The results showed that the plant species Philodendron has a value > 1, it shows that the commodity meets the superior criteria with an LQ value of 2.3299.